Very efficient correlator for loosely synchronised codes - Pérez, M. C. (2010)
A new approach for the efficient correlation of loosely synchronised (LS) codes, when they are generated from Golay pairs, is presented. By employing this new approach, the total number of operations to be performed in the correlation is notably decreased, if compared with existing proposals based on classical efficient Golay correlators or straightforward methods. The proposed correlator can be easily implemented on configurable hardware devices to achieve real-time operation even with long codes.